Modern issues of sugar beet (Beta vulgaris L.) hybrid breeding - S. D. Karakotov; I. V. Apasov; A. A. Nalbandyan; E. N. Vasilchenko; T. P. Fedulova (Вавиловский журнал генетики и селекции)
High efficiency of the cultivation of unfertilized sugar beet ovules and preparation of haploid regenerants (microclones) of pollinators – maintainers of О-type sterility and MS forms of the RMS 120 hybrid components has been shown. A technological method that accelerates the creation of new uniform starting material is proposed. It speeds up the breeding process two to threefold. The identification of haploid regenerants with sterile cytoplasm in initial populations is of great theoretical and practical importance for breeding, as it facilitates the production of homozygous lines with cytoplasmic male sterility and high-performance hybrids on sterile basis. As shown by molecular analysis, a single-nucleotide polymorphism never reported hitherto is present in the mitochondrial genome of the haploid plant regenerants. It allows identification of microclones as fertile and sterile forms. It has been found that DNA markers of the sugar beet mitochondrial genome belonging to the TR minisatellite family (TR1 and TR3) enable reliable enough identification of haploid microclonal plants as MSor O-type forms. Fragments of 1000 bp in length have been detected in monogenic forms in the analysis of 11 sugar beet plants cultured in vitro by PCR with the OP-S4 random RAPD primer. Testing of the OP-S4 marker’s being in the same linkage group as the genes responsible for expression of the economically valuable trait monogermity demonstrates its relative reliability. By the proposed method, dihaploid lines (DH) of the male-sterile form and the О-type sterility maintainer of the RMS 120 sugar beet hybrid have been obtained in in vitro culture. These lines are highly uniform in biomorphological traits, as proven under field conditions.